2019
DOI: 10.15171/jcs.2019.002
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Women with Cancer and Its Influencing Factors

Abstract: Introduction: Studies show that some of the factors such as pain and psychological changes could decrease the quality of life of patients with cancer. The understanding of these factors can enhance the effectiveness and process of cancer treatment. Therefore this study was conducted to investigate the quality of life in women with cancer and its influencing factors. Methods: This was a cross-sectional study which was carried out in the city of Tabriz in the northwestern part of Iran in 2016. The sample consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
7
3
1
Order By: Relevance
“…Our ndings showed that the quality of life of the patients in our study was fair. The mean overall quality of life score in our study was higher than that reported in previous studies [20][21], probably because their studies included only breast cancer patients and was carried out in Iran where contextual factors could have in uenced participants' perception of their general health. However, our mean value was lower compared to other studies [16,[18][19].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Our ndings showed that the quality of life of the patients in our study was fair. The mean overall quality of life score in our study was higher than that reported in previous studies [20][21], probably because their studies included only breast cancer patients and was carried out in Iran where contextual factors could have in uenced participants' perception of their general health. However, our mean value was lower compared to other studies [16,[18][19].…”
Section: Discussioncontrasting
confidence: 89%
“…For the functioning scales and global QOL higher scores indicate better functioning; for the symptom scales higher scores indicate higher symptom burden. In general total score ranges from 1-100 and measures quality of life of patients during the past week [16,[18][19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…In their report, age, marital status and occupation had no significant influence on QoL of the women. [15]. The outcome of this study on age was in contrast to the finding of Morrow and colleagues (2014) that, breast cancer has a greater impact on HRQoL in younger patients than in older ones [12].…”
Section: Discussioncontrasting
confidence: 83%
“…The previous studies showed similar employment outcome predictors among BCa survivors. [ 20 21 ] Reproductive state is dependent on ovarian activity exhibited by menarche at its onset and menopause at its cessation. [ 22 ] In our study population, menarche at 12 years constituted 41.6% (n = 50) and menopause at 55 years and above 36.6%.…”
Section: Discussionmentioning
confidence: 99%